3a^3b^2-6a^2b^3+27/4ab因式分解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 16:00:41
3a^3b^2-6a^2b^3+27/4ab因式分解3a^3b^2-6a^2b^3+27/4ab因式分解3a^3b^2-6a^2b^3+27/4ab因式分解3a^3b^2-6a^2b^3+27/4ab
3a^3b^2-6a^2b^3+27/4ab因式分解
3a^3b^2-6a^2b^3+27/4ab
因式分解
3a^3b^2-6a^2b^3+27/4ab因式分解
3a^3b^2-6a^2b^3+27/4ab
=3/4 ab(4a^2b-8ab^2+9)
原式=3/4ab(4a²b-8ab²+*)
A-B A+B 2B+A 3A-B 6A+2B
2(a+b)-[4(a+b)-3(a+b)]一[5(a-b)+(a-b)]过程
(a+2b)(2a+4b)(3a+6b)(4a+8b)
(a-b)^6*[-4(b-a)^3]*(b-a)^2÷(a-b)=求过程
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)
因式分解:3b(b-a)+6a(a-b)^2
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)
若a-b=4,3a+2b=6,3a(a-b)+2b(a-b)=( ).
2a-{7b+[4a-7b-(2a-6a-4b)]-3a
初二分式的加减法2a-b-c/(a-b)(a-c)+ 2b-c-a/(b-c)(b-a)+ 2c-b-a/(c-b)(c-a)3a-6b/a+b- 5a-6b/a-b- 4a-5b/a+b+ 7a-8b/b-a注:有空格的地方是下一个分式
(2a-3b)[(a+b)-b(a-3b)]
(a^2+1)(-4a^2+1)+a^4-1 3a(a-b)(a+b)-6(b-a)^2a^2-9(a-b)^2= 3a(a-b)(a+b)-6(b-a)^2=
计算:(4a-b)^2-[8a*(a-b)-(3a-b)*(3a+b)]
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/b]
2a(a-b)+4a(2a+3b)
因式分解:1、a*a*a*a+2a*a*a*b+3a*a*b*b+2a*b*b*b+b2、(a+1)(a+3)(a+4)(a+6)-280
a+a-a+2a-3a-2b+3b-5b+3b-4b-5b
(2/3a)-[2/(a+b)]{[(a+b)/3a]-a-b}÷[(a-b)/a]